Neuropsychiatric and Physical Manifestations of Post-Covid-19 Syndrome: Insights into Physical Activity and Biomarkers in the Moroccan Population - Youssef NADIR; Habiba NECHCHADI; Hicham ESSELMANI; Mohamed MERZOUKI; Karim ARIFI (Réflexions Sportives)
Several patients experience persistent symptoms that last for more than three months following the acute phase of SARS-CoV-2 infection. These symptoms, which cannot be attributed to any other diagnosis, are collectively referred to as post-Covid-19 syndrome. This study aimed to physiologically characterize Moroccan patients with post-Covid-19 syndrome, determine the prevalence of five persistent neuropsychiatric and physical manifestations, and analyze the factors associated with these symptoms. We conducted a cross-sectional study of 120 patients with post-Covid-19 syndrome in the province of Beni Mellal, Morocco. Descriptive statistics were used to summarize sociodemographic and clinical characteristics, Covid-19 status, pre-infection physical activity level. Logistic regression was used to study associations between pre-infection physical activity level and biomarkers with the manifestations of post-Covid-19 syndrome. No association was found between the level of physical activity and neuropsychiatric and physical manifestations of post-Covid-19 syndrome. When comparing the mean LDL- cholesterol concentration with pre-infection physical activity level, a significant difference was detected (P = 0.0437). The same result was observed when the HDL cholesterol concentration was compared according to sex (P = 0.0024). Fatigue was the most common symptom in the study population (67%), whereas depression was the least common symptom (10%). The logistic regression model revealed a negative association between HDL cholesterol levels and dyspnea (P = 0.0472). Pre-infection physical activity levels may influence LDL-cholesterol concentrations in post-Covid-19 syndrome patients. Lower HDL-cholesterol concentration may be linked to the persistence of dyspnea, which makes it a potential biomarker; further mechanistic investigations are needed taking gender differences into consideration.